Media Model Tiruan Sapi Perah dapat Meningkatkan Kemampuan Kognitif Anak Usia Dini - Wardah Suweleh; Meirza Nanda Faradita (Proceedings of The ICECRS, 2019)
The initial conditions indicate that the cognitive abilities of early childhood are still low in understanding the workings of cow milking. In the activity of milking cow's milk, children's cognitive abilities are needed so that the results obtained can be maximized. Based on observations on February 4, 2019, researchers found that many early childhood children are afraid of milking cows, there are also students who do not understand how to milk cows to obtain milk with large capacity. Therefore, the researchers used the artificial cow model artificial media. This model is a three-dimensional imitation model with a length of 120cm x 75cm. this model is used so that students can listen to the process of milking the cow properly, so that students can practice directly properly and correctly. The subject and location of this study were group B RA Nurul Islam, Boro Village RT 01 / RW 01, Tanggulangin Subdistrict, Sidoarjo Regency with subjects as many as 14 PAUD students consisting of 10 male students and 4 female students. This type of research is classroom action research (PTK) carried out in two cycles, data collection techniques used are teacher observation sheet instruments, student observation sheets and practice test sheets milking cows with three-dimensional imitation dairy media media. The results showed an increase in children's cognitive abilities in the practice of milking cows with a three-dimensional imitation model of dairy cows reaching a developmental percentage of 64.28%, and increasing in the second cycle of 92.8%. Then the results of observation of teacher activities in the first cycle were 65.5% which increased by 22% to 87.5% in cycle II. While observations of student activities obtained results of 64.28% results in the first cycle, and 85.7% results in the second cycle. Each aspect of a child's cognitive abilities in understanding how to milk a cow with increased dairy cow media in the second cycle has achieved a predetermined indicator of success so it does not need to be increased in the next cycle. Based on the results of the research described above, it can be concluded that the medium of dairy cows can improve children's cognitive abilities in understanding and practicing milking with dairy cow three-dimensional model media in group B RA Nurul Islam Boro Village RT 01 / RW 01 Tanggulangin District Sidoarjo.